ANALISIS PENATAAN ASET TETAP PADA BADAN PENGELOLAAN KEUANGAN DAN ASSET DAERAH KOTA JAYAPURA - Maranatha Siregar; Westim Ratang; Syaikhul Falah (Universitas Cenderawasih, 2020)
One of the problems that often arise in the management of regional property is the administration of regional property. In the implementation of the Asset Administration, it is often constrained in terms of reporting the assets of certain Regional Apparatus Organizations. This is because there is no Standard Operating Procedure in terms of the Administration of these Assets, which causes delays in the preparation of Regional Government Financial Reports (LKPD). The causes of administrative side problems are incomplete documents and unclear deletion findings, financial side causes, namely budget constraints, delegation and misuse of maintenance costs, causes of bureaucracy, namely the absence of a legal umbrella, limited responsibilities of BPKAD, non-centralized procurement of vehicles, causes of human resources namely the level of employee mutation and limited human resources and the causes of limitations in the use of regional property management information systems, namely SIMDA BMD still using an off-line system and SIMDA BMD in the City Government of Jayapura has not been integrated into the financial department of BPKAD.